Development of a bio-refinery process for the production of speciality chemical, biofuel and bioactive compounds from Laminaria digitata - Kostas, Emily T.; White, Daniel A.; Cook, David J. (Elsevier, 2017)
The development of cascading bio-refinery processes that are capable of producing a range of valuable products is of increasing significance and will help to ensure that mankind makes efficient usage of bioresources. Seaweed feedstocks have the potential to be refined into fractions used for biofuel production, as renewable sources of platform chemicals or for a range of potentially interesting bioactive compounds. This study describes the development of a putative bio-refinery approach using Laminaria digitata as feedstock. Firstly, the commercially valuable polysaccharides fucoidan and alginate were extracted. Analysis of the monosaccharide and sulphate contents of the fucoidan extract confirmed its isolation with a purity of ca. 65%. Analysis of the composite residue remaining after extraction of alginate and fucoidan from L. digitata showed an increase in crude fibre content, of which the predominant monosaccharide was glucose (161.9 mg glucose per g residue), making this residue a potential feedstock for bioethanol production. After dilute acid hydrothermal pre-treatment (1.5 N H2SO4, 24 min, 121 °C, 25% [biomass/reactant] solids loading) and enzymatic saccharification of this residue, a 93.8% of theoretical glucose yield was achieved. This hydrolysate was fermented using Saccharomyces cerevisiae NCYC2592 and a yield of ca. 94.4% of the theoretical ethanol yield was achieved. To add value to the biorefining process, waste streams from the production of alginate, fucoidan and bioethanol were collected and screened for a range of bioactivities. Subsequently, a methanol extract prepared from the liquor waste stream which remained after polysaccharide extraction was shown to exhibit both anti-oxidant (EC50 15.3 mg/mL) and anti-microbial activity against the human bacterial pathogen Burkholderia cenocepacia. The identification of extracts with bioactive attributes which have been recovered from a seaweed-based bio-refinery process is novel, and offers a potential route through which added value can be derived from natural resources such as L. digitata.